Experimental Study on the Hole-Forming Process at the Borehole Bottom During Hot Water Drilling in Ice and Its Influence Mechanisms - Zhipeng Deng; Youhong Sun; Xiaopeng Fan; Pavel Talalay; Yifan Yang; Ximu Liu; Da Gong; Bing Li; Ting Wang; Wei Wu; Nan Zhang; Xianzhe Wei (Journal of Marine Science and Engineering, 2025)
Hot water drilling is a drilling method that employs high-temperature and high-pressure hot water jetting to achieve ice melting drilling. Characterized by rapid drilling speed and large hole diameter, it is widely used for drilling observation holes in polar ice sheets and ice shelves. Understanding the hole-enlargement process at the bottom of hot water-drilled holes is crucial for rationally designing the structure of hot water drills. However, due to the complexity of heat transfer processes, no suitable theoretical model currently exists to accurately predict this process. To address this, this paper establishes an experimental platform for hot water drilling and conducts 24 sets of experiments under different drilling parameters using visualization techniques. The study reveals the influence mechanisms of drilling speed, hot water flow rate, hot water temperature, downhole drill shape, and nozzle structure on the hole-forming process at the borehole bottom. Experimental results indicate that the primary hole enlargement occurs near the nozzle, achieving 69–81% of the theoretical maximum borehole diameter. The thermal melting efficiency at the borehole bottom is approximately 80%, with about 20% of the input hot water energy heating the surrounding ice. Under identical hot water parameters, jet shapes and drill shapes exhibit minimal impact on borehole geometry. But the improvement of the jet speed and hot water temperature can accelerate the hole-forming process.